Strategi managemen pembinaan prestasi dalam meningkatkan kinerja klub sepak bola studi kasus pada klub sepak bola putri neo angel tahun 2024 - Nadya Sari Fadlillah; Soemardiawan; Sri Erny Muliyani (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2024)
The background to this research is the lack of facilities and infrastructure, such as fields and balls for practice and the lack of support from Asprov itself for women's football. This research aims to find out how the achievement coaching management strategy is implemented at the Neo Angel women's soccer club, to find out whether internal and external factors influence the success of the achievement coaching management strategy at the Neo Angel women's soccer club, and to find out the impact of the achievement coaching management strategy on individual career development of female soccer players at the Neo Angel club. The research design used is a qualitative descriptive method. The instruments used are observation instruments, questionnaires and documentation. The population is the Neo Angel club, totaling 38 people, the sample is 16 people consisting of 3 managers, 3 coaches and 10 players. The data analysis technique used is data triangulation technique. Data analysis by collecting data, reducing data, presenting data and drawing conclusions. The results of this research show that the strategy implemented by Neo Angel includes designing and developing a road map for player performance to improve club performance in the short and long term, as well as developing cooperation with sponsors and related parties. Internal factors that influence club performance, include clear and open communication with players and technical staff, close collaboration between club management and coaches